Biomechanical Measurement Error Can Be Caused by Fujifilm Thickness: A Theoretical, Experimental, and Computational Analysis. (16th August 2017) - Sarwar, Ahmed; Srivastava, Simli; Chu, Chris; Machin, Alan; Schemitsch, Emil H.; Bougherara, Habiba; Bagheri, Zahra S.; Zdero, Radovan
Abstract : This is the first study to quantify the measurement error due to the physical thickness of Fujifilm for several material combinations relevant to orthopaedics. Theoretical and experimental analyses were conducted for cylinder-on-flat indentation over a series of forces (750 and 3000 N), cylinder diameters (0 to 80 mm), and material combinations (metal-on-metal, MOM; metal-on-polymer, MOP; metal-on-bone, MOB). For the scenario without Fujifilm, classic Hertzian theory predicted the true line-type contact width as W O = { ( 8 F D c y l ) / ( π L c y l ) [ ( 1 - ν c y l 2 ) / E c y l + ( 1 - ν f l a t 2 ) / E f l a t ] } 1 / 2, where F is compressive force, D c y l is cylinder diameter, L c y l is cylinder length, ν c y l and ν f l a t are cylinder and flat Poisson's ratios, and E c y l and E f l a t are cylinder and flat elastic moduli. For the scenario with Fujifilm, experimental measurements resulted in contact widths of W F = 0.1778 × F 0.2273 × D 0.2936 for MOM tests, W F = 0.0449 × F 0.4664 × D 0.4201 for MOP tests, and W F = 0.1647 × F 0.2397 × D 0.3394 for MOB tests, where F is compressive force and D is cylinder diameter. Fujifilm thickness error ratio W F / W O showed a nonlinear decrease versus cylinder diameter, whilst error graphs shifted down as force increased. Computational finite element analysis for several test cases agreed with theoretical and experimental data, respectively, to within 3.3% and 1.4%. Despite its wide use, Fujifilm's measurement errors must be kept in mind when employed in orthopaedic biomechanics research.